DEVELOPMENT OF LABORATORY COURSE JOBSHEETS TO IMPROVE THE EFFECTIVENESS OF STUDENT WORK LATHE - Koto, Indra; Lubis, Rahmat Alfath (Universitas Pendidikan Indonesia, 2023)
Lathe machining jobsheet are designed to help students participate in practicum activities, make them a guide during practicum and increase time efficiency. This research was conducted to increase the effectiveness of students' lathe work on lathe machining jobsheets and to find out the feasibility of how the jobsheet was developed. This type of research is carried out using a research and development approach with the steps of Define, Design, Development, and Dissemination. Jobsheet trials were conducted on three students majoring in machining, the results of the student trials assessed that the jobsheets developed were very feasible with a feasibility percentage of 92%. Due diligence by media experts is very feasible with a percentage of 92.5%. The feasibility test by material experts was considered very feasible with a percentage of 93.5%. Overall jobsheet eligibility is very feasible with an accumulated eligibility percentage of 92.88%.